Inventing the Past: Remarks on the Re‑enactment of Medieval Poetry - Folkart, Barbara (TTR, 1998)
AbstractInventing the Past : Remarks on the Re-enactment of Medieval Poetry — No matter how qualified she may be from the philological standpoint, the translator of medieval poetry is immediately confronted with a sense of her own diachronic incompetence insofar as the cultural, esthetic and affective resonances of the medieval poem are concerned.The translator who chooses to produce a crib will give the modern reader a way into the surface structures of the medieval text, but will convey little of its emotional resonance. Opting for prose translation will allow her to flesh her reading out somewhat, but convey none of the meaning inherent in the form itself. Even verse translation — if it remains merely verse — will prove inadequate to the "poetry" of the original text. The only way to give the twentieth-century reader a way into the jouissance of the medieval poem, as opposed to its syntax and semantics, is to function as a poet, and produce a free-standing text.This essay discusses various writerly strategies for reactivating the poetry of the medieval poem, for producing feeling, and the sort of insight that can come only from feeling. Illustrating these considerations are a number of "derived poems" of my own, based on pieces by Charles d'Orléans.